ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR PERHOTELAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA MASA PANDEMI COVID-19 - Muhamad Ryan Nur Ali (2021)
This research is a quantitative study that aims to determine the effect of Working Capital Turnover, Debt To Asset Ratio, Current Ratio on Return On Assets in Hospitality Companies on the Indonesia Stock Exchange in 2018-2020. The method of determining the sample used purposive sampling and obtained 24 samples of companies that met the criteria and 72 firm-year observations. The type of data used in this research is secondary data. Testing data analysis, namely validity and reliability testing and hypothesis analysis, in this study using PLS (Partial Least Square) analysis with the smartPLS version 3.0 program and a significance level of 5% (0.05). with the Smart PLS 3.0 program. The results of this study indicate that Working Capital Turnover, Debt To Asset Ratio, Current Ratio have no significant effect on Return On Assets.